Berço manuelino from the wreck of Santiago - Pawel Kardasz (Gladius)
The breech-loading rail guns appeared in Europe in the 15th century, and in the next century they were widely used as light naval artillery. They were characterized by a high rate of fire, thanks to the use of replaceable chambers a mug-shaped device called a chamber or breech block, previously charged with gun powder and a projectile. In Portugal they were called ‘berço’, called ‘verso’ in Spain. These guns were commonly found on board ships sailing East on the Carreira da India during the reign of King D. Manuel I and earned the nickname ‘manuelino’ after this ruler. A berço manuelino marked Durr 876 is housed in the KwaZulu Natal collection in Pietermaritzburg, South Africa. This cannon was salvaged from the Santiago shipwreck that sank in the Bassas da India atoll in the Mozambique Channel in 1585. It is an excellent example of the berço manuelino from the period of their widespread use in the Portuguese fleet. Its condition is satisfactory, considering that the cannon lay for 400 years on a coral reef flooded by sea waves. Berço manuelino Durr 876 witnessed one of the most famous and tragic maritime disasters of the 16th century, described in numerous accounts.